2023
DOI: 10.1039/d2nj05790e
|View full text |Cite
|
Sign up to set email alerts
|

Hole-transport materials based on the terthienyl core unit for efficient perovskite solar cells

Abstract: Thiophene and oligothiophenes have outstanding electronic properties, especially their electron-rich nature of would endow good interfacial contact with perovskite layer, making them an ideal building blocks for hole transport materials...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recently, our group also reported oligothiophene-based HTM THP-1 and successfully employed it in PSCs. 44 During the optimization, we found that the deep-lying highest occupied molecular orbital (HOMO) energy level of THP-1 results in insufficient charge transfer driving force and thus affects the PSC device performance. To increase the HOMO energy level of conjugated materials, the addition of electron-giving groups is one of the most successful methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group also reported oligothiophene-based HTM THP-1 and successfully employed it in PSCs. 44 During the optimization, we found that the deep-lying highest occupied molecular orbital (HOMO) energy level of THP-1 results in insufficient charge transfer driving force and thus affects the PSC device performance. To increase the HOMO energy level of conjugated materials, the addition of electron-giving groups is one of the most successful methods.…”
Section: Introductionmentioning
confidence: 99%